Estudio de las Organizaciones de la Economía Popular y Solidaria en la Parroquia Taquil del Cantón Loja. - Solórzano Cabrera, Marco Andrés (2018)
he present research work entitled "STUDY OF THE ORGANIZATIONS OF THE POPULAR AND SOLIDARITY ECONOMY IN THE TAQUIL PARISH OF CANTON LOJA" was developed as an instrument of contribution for the development of the Economic, Popular and Solidarity sector, starting from the study of its conceptual bases and of methodological contributions from critical theory, as well as proposals from several authors that allowed to clarify the complete panorama of the object of study, as well as to evaluate the intervention made by EPS organizations in the economic and social conditions of the studied population. With the development of the work, the proposed objectives were met, such as evaluating the forms of cooperation and solidarity that coexist within the framework of the Popular and Solidarity Economy in the Taquil parish of Loja, for which a field investigation was used. means of the techniques such as observation, interviews and georeferencing, making an analysis to establish the intervention of the Solidarity Popular Economy (EPS) in the parish. At the same time, the specific objectives were proposed focusing first on the characterization of the socioeconomic aspects in the framework of the popular and solidarity economy, allowing to know the socio-cultural data of the parish as well as the economic-productive ones helping to prioritize all the problems and potentialities that are immersed in the parish, it was also determined that there are six organisms that are offering their products and services to the inhabitants and working continuously to promote social and community development, however they are not working under legal standards, due to the lack of help and control from the regulatory bodies, the lack of financial organizations that can support the economic-productive growth of the sector was also identified. The second objective was to diagnose the intervention of the entities of the popular and solidary economy, for which a workshop was held with all the organizations present in the parish obtaining the main economic-financial problems that exist in it, to later build a tree of problems, then develop a tree of objectives that allowed to counteract the problems presented and thus pose possible alternative solutions to subsequently conduct a qualitative and quantitative analysis of the alternatives determining that the most viable alternative is to train organizations in accounting-financial issues to then create a savings bank that will solve the 5 problems found in the parish and improve the functioning of existing organizations, achieving the integration and support of the entire Taquile community. The last objective was to design a financial proposal with solidarity values and territorial relevance for the parish, applying the Logical Framework Matrix, in order to identify the strategies and purposes. Finally, with the work carried out it is concluded that the intervention of the forms of cooperation of the Popular and Solidarity Economy in the parish has been a fundamental pillar in the social and economic development of each inhabitant, since with the formation of organizations a entrepreneurial culture and employment has been generated, which are essential to develop the skills and abilities of the inhabitants, thus improving their quality of life and contributing to the socio-economic development of the sector.